Automated identification of complex undercut features for side-core design for die-casting parts. (September 2014) - Singh, Ranjit; Madan, Jatinder; Kumar, Rajesh
This article describes automated identification, classification, division and determination of release direction of complex undercut features of die-cast parts. The proposed system uses the concepts of visibility and accessibility to identify undercut features from a B-rep model of a die-casting part. The undercut features are then classified using a rule-based algorithm. Thereafter, the identified complex undercut features are separated into simple ones. Finally, the release direction for each simple undercut feature is determined and those having common release direction are grouped. The proposed system is implemented on case study die-cast parts, and the results are verified. This article would help bridge the design-manufacturing integration gaps in the die-casting process.